Effects of Four-Week Intake of Blackthorn Flower Extract on Mice Tissue Antioxidant Status and Phenolic Content - Vedran Balta; Domagoj Đikić; Irena Crnić; Dyna Odeh; Nada Orsolic; Ivana Kmetič; Teuta Murati; Verica Dragović Uzelac; Irena Landeka Jurčević (Polish Journal of Food and Nutrition Sciences)
The study examined the antioxidative physiological effects of phenolics from an ethanol-water extract of blackthorn flowers orally administrated to C57/BL6 mice for 28 days in daily doses of 25 mg of total phenolics/kg body weight. Contents of phenolics in the intestine, liver, and kidneys collected after 1, 7, 14, 21, and 28 days of extract administration were analyzed by UPLC-MS/MS method. In the same tissues, the antioxidative properties were determined as ferric reducing antioxidant power (FRAP), ABTS•+ scavenging activity, content of reduced glutathione (GSH), and activity of superoxide dismutase (SOD) and catalase (CAT). The lipid peroxidation in tissues was also evaluated by thiobarbituric acid reactive substances (TBARS) assay. The exposed mice (compared to the control ones) had a lower content of TBARS in all tissues mostly on the third/fourth week of daily consumption. SOD activity and GSH content increased on the 28th day in tissues. CAT activity was higher only in the liver after one week of consumption but remained unchanged in other organs throughout the experiment. Phenolic profiles were different in individual tissues. The most prominent increases compared to the control were determined for contents of 3- O -feruloylquinic acid, 4- O-p -coumaroylqiunic acid, kaempferol pentoside, and quercetin rhamnoside in the intestine; for ferulic acid and quercetin 3- O -rutinoside in the liver; and for quercetin 3- O -rutinoside, ferulic acid, and 4- O-p -coumaroylquinic acid in the kidneys. The screened phenolics with different distribution in tissues could be responsible for slight differences in the recorded antioxidative effects.